Characterization of Al-induced electroless tin films on mild steel substrate for corrosion protection. (9th April 2020) - Singh, Prakash Chandra; Ghosh, Swatilekha
Abstract: Al-induced electroless process is used to fabricate Sn films on the mild steel substrates. The deposition reaction was performed by designing a Fe-Al galvanic couple where the optimum geometric area ratio between Fe-Al was 0.3. Additionally, NaBH4 and NaH2 PO2 reducing agents were also added to enrich the deposit morphology and composition. The film surfaces were characterized by scanning electron microscopy, energy-dispersive x-ray spectroscopy and x-ray diffraction measurements. The analysis showed dense, uniform tin deposits with the presence of boron and phosphorous. The x-ray diffraction results confirmed the polycrystalline tetragonal structure with mostly (211) texture having an average 18 nm crystallite size. The anti-corrosion performance of these tin films has been studied by immersion in saltwater, open circuit potential measurement test, potentiodynamic polarization test, and electrochemical impedance spectroscopy. The effect of the coating thickness was also considered in anti-corrosion performance. The analysis showed the tin coated steel has commendable corrosion resistant property and the corrosion rate can be decreased up to 16 times with the addition of these coatings irrespective of the film thickness.